PENGETAHUAN DAN KETERAMPILAN BIDAN DALAM PENANGANAN AWAL PREEKLAMSI SEBELUM DAN SESUDAH PELATIHAN - Simbolon, Juana Linda; Pakpahan, Sulastry (JURNAL HEALTH REPRODUCTIVE, 2018)
The aim of this study was to determine the differences in the level of knowledge and skills of midwives in the early management of pre-eclampsia in pregnancy